English Morphological Awareness in Complex Words through Color Coding for Reading Comprehension (Journal of Namibian Studies : History Politics Culture, 2023)
This study aimed to construct a hybrid learning model that underlines morphological awareness of complex words through color coding for reading comprehension. Path analysis was used to evaluate the relationship between non-English major undergraduates' morphological awareness of complex words related to lexical inferencing ability and their success in reading comprehension. The instruction and tests, including the pre-test, practice test, and post-test, were administered in the classroom and online via teaching applications. The participants were 200 non-English major undergraduates from a business administration faculty. The results indicated that the hybrid learning model had measured validity and reliability. Color coding on derivational and inflectional morphemes was a significant moderator of morphological awareness, lexical inferencing ability, and reading comprehension.